METODE KESHAHIHAN HADITS â€œAL-MUSTADRAKâ€ DALAM KITAB AL-MUSTADRAK â€˜ALA SHAHIHAIN - Mohammad Fattah; Muridatul Qutsiyah; Indri Maryani (Bayan lin-Naas : Jurnal Dakwah Islam, 2020)
This research article examines the method of authenticity of the hadith "al-mustadrak" in the book of al-mustadrak 'ala sahihain. The research method used is the library research method, namely research carried out through collecting data or scientific writings that are literary in nature to solve a particular problem or study. The focus and purpose of this research is to know and describe a brief biography of Imam al-Hakim Al-Naysaburi, and to know the method of authenticity of the hadith "al-mustadrak" in the book of al-mustadrak 'ala sahihain. The results of the study show that first, Imam al-Hakim Al-Naysaburi is a person who studies hadith which in the course of his life which lasted for approximately 84 years, al-Hakim has made many contributions in the field of hadith through his monumental work al-Mustadrak 'ala Shahihain. Second, in determining the validity of the hadith, al-Hakim uses a pure method of ijtihad reasoning and divides the concept of ijtihad into four points of view, namely: (1) judging from the criteria for the validity of the hadith; (2) seen from the classification of hadith; (3) seen from the approach of sanad and matan status; and (4) seen from the standard of determining the validity of the hadith.